Marketing Mix Strategy for Mitraguna Berkah Financing Products at Bank Syariah Indonesia Renon Denpasar Branch Office - Siti Rohmawati; Kusjuniati; R. Agrosamdhyo (International Forum of Researchers and Lecturers, 2023)
Bank Syariah Indonesia Renon Denpasar Branch Office as an institution engaged in the financial sector is certainly inseparable from marketing strategies as a support for its growth and development. The marketing strategy aims to support banks in achieving success and as a measure of banking performance. So that a marketing mix is also needed to achieve banking goals and objectives so that it can increase the number of customers in the bank. The focus of the research 1. How is the marketing mix strategy of mitraguna blessing financing products in increasing the number of customers at PT Bank Syariah Indonesia Renon Denpasar Branch Office? 2. What are the obstacles faced in implementing the marketing mix strategy for mitraguna blessing financing products to increase the number of customers at PT Bank Syariah Indonesia Renon Denpasar Branch Office? Research Objectives 1. To find out the application of the marketing mix strategy of financing mitraguna blessing in increasing the number of customers at PT Bank Syariah Indonesia Renon Denpasar Branch Office. 2. To find out the obstacles faced in implementing the marketing mix strategy of financing products mitraguna blessing to increase the number of customers at PT Bank Syariah